KAJIAN FOLKLOR DAN NILAI EDUKASI PADA PERMAINAN TRADISIONAL MASYARAKAT MELAYU KAPUAS HULU - Hajar Aswati; Ahmad Rabi’ul Muzammil; Agus Syahrani (Universitas Tanjungpura, 2021)
AbstractThis research aims to describing the culture of traditional Malay games in Kapuas Hulu. This research discusses the function, value of education, and the archaic words. This research is qualitative with descriptive method. The data source of this research is informants with the data form Kapuas Hulu traditional Malay games and the values contained therein. Based on the results of data analysis found 13 Kapuas Hulu traditional Malay games, include antu labok, antu tikam, antu unyar, guli, kelayang, lamong batu, lem-lem tak, pelopak, tabak, sempalai, sopet unang, pangkak gasen, and rumak perau. There are five functions contained in the Kapuas Hulu traditional Malay games is developing logical intelligence, interpersonal emotional intelligence, kinesthetic intelligence, natural intelligence, and as a means of recreation. The educational values contained in traditional games consist of 15 data and eksist 10 archaic words. The implementation plan of learning the results of this research is combined with Indonesian language learning in grade VII junior high school / equivalent level in the curriculum 2013 with KD 4.6 presenting data on a series of activities in the form of procedural text (how to play regional musical instruments, regional dances, how to make souvenirs, etc) .Keywords: Folklore, Kapuas Hulu Malay, Traditional Games